Mata Ketiga Untuk Tuna Netra Menggunakan Sensor Ultrasonik dan Arduino Pro mini328 - Fitri Nova (Elektron : Jurnal Ilmiah, 2019)
Blind people have limited physical condition. This condition makes the blind use sticks as a guide in their daily activities. With advances in technology, the stick used was replaced with a device used on the wrist by using an ultrasonic sensor and Arduino Promini 328. The ultrasonic sensor works by utilizing ultrasonic waves as transmitters and calculating distances with differences in time difference. Ultrasonic sensor sensitivity from 2 cm to 200 cm. The data processor used was the Arduino Pro Mini 328 microcontroller and the Esp8266 nodemcu with input in the form of sound issued by the Raspberry Pi. Raspberry pi is placed in the user's pocket and connected to the headset to give a warning when the ultrasonic sensor is active. This tool can also detect a distance of 45 cm ahead and 65 cm down.